DEVELOPMENT OF THE PKN LEARNING ATTITUDE ASSESSMENT MODEL IN FOREIGN POLITICAL CULTURE AND RESULTS OF PKN LEARNING FROM STUDENTS OF DEPOK CITY VOCATIONAL SCHOOL(SMK SEMESTA CIMANGGIS) - Sri Rahayu Pudjiastuti; Sri Rumiati (UNIVERSITAS PAKUAN, 2019)
This study aims to develop a PKn learning attitude assessment model in shaping the political culture and PKn learning outcomes form students of Depok City Vocational School (SMK Semesta Cimanggis). This research method uses the Research and Development (RD). Data analysis is done to see the value of each aspect or descriptor on the questionnaire. Material experts validate one time, this is caused by the average score of the results of material validation which shows a value of 3.61 which is in the good category so that the PKn learning attitude assessment model has met the standards to be tested.The evaluation expert validates twice, this is due to the average score of the results of the evaluation of stage I evaluators still showing a value of 3.35 which included enough categories so that they did not meet the standards for testing. The model of the PKn Learning Attitude assessment model was subsequently revised according to the material expert's recommendations and comments, and the revised PKn attitude learning evaluation model was re-validated by the expert evaluation Validation by evaluation experts in Phase II showed a mean score of 3.7 which belongs to the category well. Based on these results the model of PKn learning attitude assessment is worthy of being tested. Based on interviews with teachers and students, the model of PKn learning attitude assessment was revised again. The results of revision II produced the final product model for assessing PKn' learning attitudes with democratic culture material.